# Still not sure on this one?

#### orchidpsycho

##### New member
2x-(x/2)+(x+1/4)=6x

I did this

8x-(4x/2)+(4x+4/4)=24x

8x-2x+x+1=24x

7x+1=24x

1=17x

x=1/17

Keep getting that answer no matter how I do it

#### stapel

##### Super Moderator
Staff member
How did "4x + (4/4)" become "x + 1"?

Eliz.

#### orchidpsycho

##### New member
I multiplied by common denominator of 4

2x-(x/2)+(x+1/4)=6x

2x*4 = 8x

-(x/2)*4 = 4x/2 = 2x

+(x+1)/4*4 = 4x+4/4 = x+1

6x*4 = 24x

8x - 2x +x +1 = 24x

7x+1=24x

1=17x

x=1/17

prob. wrong Thats why I am asking for help

#### orchidpsycho

##### New member
Oh sorry I wrote it wrong

How did "4x + (4/4)" become "x + 1"?
2x-(x/2)+(x+1)/4=6x

8x-(4x/2)+(4x+4)/4=24x

#### stapel

##### Super Moderator
Staff member
If you mean what you posted, "4x + (4/4)", then this simplifies as "4x + 1". If, on the other hand, you omitted grouping symbols and actually meant "(4x + 4)/4", then this simplifies as "x + 1".

Since I can't tell what the original equation is supposed to be, I'm afraid I can't comment on your solution. Sorry.

Eliz.

#### orchidpsycho

##### New member
I redid it above but posted almost the same time you did. Not sure if you saw it. Thanks alot.

Hopefully its right b/c I keep getting same answer

#### stapel

##### Super Moderator
Staff member
On what basis are you saying the solution is incorrect? It doesn't match the answer in the back of the book? You plugged it back into the original equation and it didn't "work"?

Thank you.

Eliz.

#### orchidpsycho

##### New member
No answers in the back. Only odd problems and we do the even ones. I think its right I just wanted to make sure.

Thanks

#### Gene

##### Senior Member
I'll take a shot at it.
2x-(x/2)+(x+1/4)=6x
2x*4 = 8x
(x/2)*4 = 4x/2 = 2x
(x+1)/4*4 = 4x+4/4 = x+1
(x+1/4)*4 = 4x+1 or
((x+1)/4)*4=x+1

6x*4 = 24x
8x - 2x +x +1 = 24x
7x+1=24x
1=17x
x=1/17
If it is x+1/4 it is not 1/17
If it is (x+1)/4, 1/17 is right.

#### Denis

##### Senior Member
BUT if it is (x + 1/4) as it appears: 2x-(x/2)+(x+1/4)=6x

then 2x - x/2 + x + 1/4 = 6x
....x = 1/14